FROM THE EXPERIENCE OF ORGANIZATION OF SCIENTIFIC, EDUCATIONALMETHODICAL AND EDUCATIONAL ACTIVITY OF THE DEPARTMENT OF HISTORY OF PEDAGOGY AND COMPARATIVE PEDAGOGY - Боярська-Хоменко, А.; Денисенко, А. (New Collegium, 2020)
In the article features of scientific, educationalmethodical and educational work of the chair of the history of pedagogy and comparative pedagogy of the H.S. Skovoroda Kharkov National Pedagogical Univer- sity was uncovered. Methods of creative application of pedagogical ideas H.S. Skovoroda in the activity of the teachers of the department were demonstrated. The system of teaching and methodical work of the depart- ment is imbued with the idea of related work, it reveals it through the lens of pedagogical activity. Teachers of the department take into account the principle of conscious learning of students all the time. Each lesson combines different sources of knowledge acquisition. in their educational and methodical work the teach- ers of the department focus students' attention on the depth of Ukrainian educational traditions, on the thor- ough historical and pedagogical heritage of Ukrainian scientists, teachers, philosophers, thinkers. Holding the annual scientific and practical conference «H.S. Skovoroda — the outstanding Ukrainian philosopher and enlightener» is a good tradition of the department. At the conference topical issues of philosophical depth, literary creativity, wealth of pedagogical ideas H.S. Skovoroda are discussed. The members of the depart- ment provide comprehensive education of students in the extra-curricular time. They organize meaningful leisure, educational hours, round tables, meetings of discussion clubs, brain rings, wall making and more. The faculty members love their science and instill this love for their students.